THE POWER OF UNITED STATES IN DOMINATING MIXED MARTIAL ARTS SPORTS THROUGH ULTIMATE FIGHTING CHAMPIONSHIP - Aryowiloto, Julang; Rofiyarti, Fitri (jfpublisher, 2023)
The United States of America (USA) dominates in almost every aspect globally, including the sport of mixed martial arts (MMA). Most of the MMA sports promotion companies that dominate the global market are from the US. One of the largest and most popular is the UFC. As a global company, UFC is the most dominant MMA sports competition promoter in the world today due to its global economies of scale. Since its inception in the US, the UFC has developed into competitions held in several countries, such as Canada, the UK, Russia, Brazil, Uruguay, the United Arab Emirates, Australia, New Zealand, South Korea, and Singapore. This research aims to find out the UFC’s business strategy as a global company in globalizing its commodities to dominate the mixed martial arts (MMA) sports industry on a global scale. This research uses a descriptive qualitative method accompanied by a 4P Marketing Mix perspective as an analytical tool in examining the strategies implemented by the UFC. This research concludes that the UFC’s global marketing strategy is to implement various marketing elements from upstream to downstream optimally so as to be able to dominate the market share of the global MMA sports industry.